Writing and doing action research - McNiff, Jean (Thousand Oaks, California SAGE Publications, Incorporated, 2014)
The chapters in this book develop a working framework and contain worked examples and exercises to make sure that readers get the best results from their research and are fully versed in all the practical aspects of doing action research.
What do you need to know about action research in order to write it? -- What do you need to know to write action research? Why do you need to know it? -- What do you write in an action research text? -- What is the form of an action research text? -- Becoming a writer -- Writing a good quality text -- Planning for the production of texts -- Writing proposals -- Masters and doctoral dissertations and theses -- How will the quality of your action research dissertation/thesis be judged? -- Writing for academic and professional journals -- Writing your first academic book -- The significance of your action research text -- Some implications -- where next?
Keywords: Action research; Report writing